Guillain-Barré syndrome and posterior reversible leukoencephalopathy syndrome: a rare association - Joshi, Stuti (BMJ Case Rep, 2020)
A 69-year-old woman presented with headaches and visual disturbance in the context of marked hypertension secondary to non-compliance with antihypertensive medications. She developed seizures and hyperreflexia, and MRI brain showed changes consistent with posterior reversible encephalopathy syndrome (PRES). She was treated with antihypertensives with the resolution of symptoms. Over the following week, she developed progressive distal sensory loss, weakness and areflexia. The cerebrospinal fluid examination demonstrated albuminocytologic dissociation, and electrophysiological findings were in keeping with a diagnosis of Guillain-Barré syndrome (GBS). She was treated with intravenous immunoglobulin with gradual recovery. The co-occurrence of PRES and GBS has only been described in a handful of cases. In the majority of these, the dysautonomia of GBS leads to profound hypertension and subsequently PRES. This is a rare case of PRES preceding and possibly even triggering the onset of GBS. In this report, we review the literature and discuss the potential pathogenic mechanisms for this unusual association.